2011
DOI: 10.1016/j.ejphar.2011.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin extracted from medicinal Chinese herbs exerts anti-inflammatory effect via proteasome inhibition

Abstract: Shikonin, extracted from medicinal Chinese herb (Lithospermum erythrorhizo), was reported to exert anti-inflammatory and anti-cancer effects both in vitro and in vivo. We have found that proteasome was a molecular target of shikonin in tumor cells, but whether shikonin targets macrophage proteasome needs to be investigated. In the current study, we report that shikonin inhibited inflammation in mouse models as efficiently as dexamethasone. Shikonin at 4 μM reduced the Lipopolysaccharides (LPS)-mediated TNFα re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 34 publications
4
92
0
1
Order By: Relevance
“…Treatment with SHK reportedly caused cell death in various cancer cell lines, and a low dose of SHK (<3 µM) induced apoptosis in a human non-small cell lung cancer cell line, A549. 26) Consistent with those reports, our time-course study indicated that decreased viability was associated with DNA fragmentation and caspase-3/7 cleavage (Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
“…Treatment with SHK reportedly caused cell death in various cancer cell lines, and a low dose of SHK (<3 µM) induced apoptosis in a human non-small cell lung cancer cell line, A549. 26) Consistent with those reports, our time-course study indicated that decreased viability was associated with DNA fragmentation and caspase-3/7 cleavage (Fig. 2).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in this study, we explored the effects of shikonin on IκBα degradation to examine its potential influence on NF-κB. The result showed that shikonin could antagonize the degradation of IκBα in IL-1β induced chondrocytes which also mirrored a previous study conducted in macrophage [17]. The elevated expression of IκBα induced by shikonin would appear to be beneficial for OA chondrocytes.…”
Section: Discussionsupporting
confidence: 70%
“…It has various pharmacological properties, such as wound healing [13], anti-tumor [14], antioxidant [15] and anti-inflammatory [16,17] properties. The antiinflammatory effect of shikonin was blocking NF-κB p65 translocation from cytoplasm to nucleus by accumulating high levels of IκBα protein in macrophages [17]. However, the effect of shikonin on the equilibrium between synthesis and degradation of cartilage ECM to IL-1β stimulation or its efficacy in OA treatment has not been authenticated.…”
Section: Introductionmentioning
confidence: 99%
“…The red pigments from the roots of L. erythrorhizon have been used since ancient times as dyestuffs for fabrics, cosmetics and food (Chang et al 2008), and as crude drugs for anti-inflammatory ointment (Ito et al 2011). It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%